Diagnosis of AL amyloidosis on bone marrow aspirate smears - A Case Report - Supraja Sundaram; Mamta Soni; Prabu Pandurangan; Soukat Ali (Apollo Medicine)
Introduction: An amyloidosis is a group of diseases associated with the deposition of abnormal protein fibrils in the tissues. Primary amyloidosis (AL) type is the most common form of systemic amyloidosis encountered in clinical settings resulting from the deposition of abnormal light chains associated with underlying plasma cell dyscrasia. Amyloid deposits are rarely seen in bone marrow aspirate smears. Methods: Amyloidosis occurs as a result of the deposition of autologous proteins, which, when viewed under a light microscope, appear as eosinophilic, acellular, amorphous deposits. Results: We presented a case of AL amyloidosis presenting with cardiac manifestations and detected to have amyloid deposits in bone marrow aspirates. Conclusion: To the best of our knowledge, reporting amyloid deposition in bone marrow aspirate smears is very rare and unusual, with sparse mention of its occurrence in literature. Careful examination of bone marrow aspirate for this striking finding leads us to a quicker diagnosis of amyloidosis for a prompt determination of therapeutic protocol, improving the outcomes for the patients.